The Antibacterial and Anti-Biofilm Activity of Metal Complexes Incorporating 3,6,9-Trioxaundecanedioate and 1,10-Phenanthroline Ligands in Clinical Isolates of Pseudomonas aeruginosa from Irish Cystic Fibrosis Patients - Megan O'Shaughnessy; Pauraic McCarron; Livia Viganor; Malachy McCann; Michael Devereux; Orla Howe (MDPI AG, 2020)
Chronic infections of Pseudomonas aeruginosa in the lungs of cystic fibrosis (CF) patients are problematic in Ireland where inherited CF is prevalent. The bacteria's capacity to form a biofilm in its pathogenesis is highly virulent and leads to decreased susceptibility to most antibiotic treatments. Herein, we present the activity profiles of the Cu(II), Mn(II) and Ag(I) tdda-phen chelate complexes {[Cu(3,6,9-tdda)(phen)2]·3H2O·EtOH}n (Cu-tdda-phen), {[Mn(3,6,9-tdda)(phen)2]·3H2O·EtOH}n (Mn-tdda-phen) and [Ag2(3,6,9-tdda)(phen)4]·EtOH (Ag-tdda-phen) (tddaH2 = 3,6,9-trioxaundecanedioic acid; phen = 1,10-phenanthroline) towards clinical isolates of P. aeruginosa derived from Irish CF patients in comparison to two reference laboratory strains (ATCC 27853 and PAO1). The effects of the metal-tdda-phen complexes and gentamicin on planktonic growth, biofilm formation (pre-treatment) and mature biofilm (post-treatment) alone and in combination were investigated. The effects of the metal-tdda-phen complexes on the individual biofilm components; exopolysaccharide, extracellular DNA (eDNA), pyocyanin and pyoverdine are also presented. All three metal-tdda-phen complexes showed comparable and often superior activity to gentamicin in the CF strains, compared to their activities in the laboratory strains, with respect to both biofilm formation and established biofilms. Combination studies presented synergistic activity between all three complexes and gentamicin, particularly for the post-treatment of established mature biofilms, and was supported by the reduction of the individual biofilm components examined.